Enhanced Dissolution and Bioavailability of Curcumin Nanocrystals Prepared by Hot Melt Extrusion Technology - Zhao Y; Xu X; Dai A; Jia Y; Wang W (International Journal of Nanomedicine, 2024)
Yujie Zhao,1 Xiaoyin Xu,1 Anyin Dai,2 Yunxiang Jia,1 Wenxi Wang1 1College of Pharmacy, Zhejiang University of Technology, Hangzhou, People’s Republic of China; 2Department of Pharmacy, The 903rd Hospital of People’s Liberation Army, Hangzhou, People’s Republic of ChinaCorrespondence: Wenxi Wang, College of Pharmacy, Zhejiang University of Technology, 18# Chaowang Road, Hangzhou, Zhejiang, 310014, People’s Republic of China, Tel +86 571 8832 0772, Fax +86 571 8832 0320, Email yjw@zjut.edu.cnPurpose: Curcumin nanocrystals (Cur-NCs) were prepared by hot melt extrusion (HME) technology to improve the dissolution and bioavailability of curcumin (Cur).Methods: Cur-NCs with different drug-carrier ratios were prepared by one-step extrusion process with Eudragit® EPO (EEP) as the carrier. The dispersed size and solid state of Cur in extruded samples were characterized by dynamic light scattering (DLS), scanning electron microscope (SEM), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). The thermal stability of Cur was analyzed by thermogravimetric analysis (TGA) and high performance liquid chromatography (HPLC). Dissolution and pharmacokinetics were studied to evaluate the improvement of dissolution and absorption of Cur by nano-preparation.Results: Cur-NCs with particle sizes in the range of 50~150 nm were successfully prepared by using drug-carrier ratios of 1:1, 2:1 and 4:1, and the crystal form of Cur was Form 1 both before and after HME. The extrudate powders showed very efficient dissolution with the cumulative dissolution percentage of 80% in less than 2 min, and the intrinsic dissolution rates of them were 13.68 ± 1.20 mg/min/cm2, 11.78 ± 0.57 mg/min/cm2 and 4.35 ± 0.20 mg/min/cm2, respectively, whereas that of pure Cur was only 0.04 ± 0.00 mg/min/cm2. The TGA data demonstrated that the degradation temperature of Cur was about 250 °C, while the HPLC results showed Cur was degraded when extruded at the temperature over 150 °C. Pharmacokinetic experiment showed a significant improvement in the absorption of Cur. The Cmax of Cur in the Cur-NC group was 1.68 times that of pure Cur group, and the Cmax and area under the curve (AUC0-∞) of metabolites were 2.79 and 4.07 times compared with pure Cur group.Conclusion: Cur-NCs can be prepared by HME technology in one step, which significantly improves the dissolution and bioavailability of Cur. Such a novel method for preparing insoluble drug nanocrystals has broad application prospects. Keywords: hot melt extrusion technology, curcumin, nanocrystals, dissolution, absorption in vivo